2010
DOI: 10.1074/jbc.m110.100941
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Embryonic Cell Division and Glycosaminoglycan Biosynthesis in Glucuronyltransferase-I-deficient Mice

Abstract: We have revealed that in Caenorhabditis elegans, non-sulfated chondroitin is required for normal cell division and cytokinesis at an early developmental stage, whereas heparan sulfate is essential for embryonic morphogenesis in the later stages of development. To clarify the roles of chondroitin sulfate and heparan sulfate in early embryogenesis in mammals, we generated glucuronyltransferase-I (GlcAT-I) knock-out mice by gene targeting. GlcAT-I is an enzyme required for the synthesis of both chondroitin sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 29 publications
(25 reference statements)
3
54
0
Order By: Relevance
“…[21][22][23]30) This finding suggests the paradoxical notion that a temporal decline in CS levels may be required for normal cell fusion processes that occur during the formation of multinucleated syncytia in somatic cells, including the formation of skeletal myogenesis. 32,33) The levels of extracellular and/or pericellular CS chains in differentiating C2C12 myoblast culture are dramatically reduced at the stage when multinucleated myotube formation begins in earnest, and this temporal reduction in CS chain abundance seems to be cell autonomously regulated by hyaluronidase-1, one of the CS catabolic enzymes.…”
Section: Cs Has An Essential Role In Pluripotency Andmentioning
confidence: 51%
See 2 more Smart Citations
“…[21][22][23]30) This finding suggests the paradoxical notion that a temporal decline in CS levels may be required for normal cell fusion processes that occur during the formation of multinucleated syncytia in somatic cells, including the formation of skeletal myogenesis. 32,33) The levels of extracellular and/or pericellular CS chains in differentiating C2C12 myoblast culture are dramatically reduced at the stage when multinucleated myotube formation begins in earnest, and this temporal reduction in CS chain abundance seems to be cell autonomously regulated by hyaluronidase-1, one of the CS catabolic enzymes.…”
Section: Cs Has An Essential Role In Pluripotency Andmentioning
confidence: 51%
“…A complementary analysis in which the bacterial CS-degrading enzyme chondroitinase ABC (ChABC) was used to remove CS selectively from wild-type, 2-cell embryos indicated that the failure of cytokinesis is causally linked to the loss of CS. 30) Taken together, these findings show that Chn/CS chains are indispensable for embryonic cell division in a manner that is conserved from worms to mammals.…”
Section: Chn/cs Has An Essential Role In Embryonic Cellmentioning
confidence: 72%
See 1 more Smart Citation
“…The ability of CS to induce stem cell proliferation has recently been documented in the nematode, and the involvement of chondroitin and CS in controlling embryonic cell division is mediated by regulating proper embryonic cytokinesis (35,92,93). Studies have also shown that CS serves as a docking site for growth factors and thereby modulates responsiveness to FGF-2 in embryonic NSPCs (94).…”
Section: Cs/ds Chains Promote Proliferation and Self-renewal Of Nspcsmentioning
confidence: 99%
“…Defects in chondroitin synthesis cause embryonic lethality with cytokinesis arrest in Caenorhabditis elegans and mice [Mizuguchi et al, 2003;Izumikawa et al, 2010]. In budding yeast, targeted vesicle fusion not only increases the surface area at the division site but also delivers enzymatic cargoes such as Chs2 for PS formation [Bi and Park, 2012].…”
Section: Ps Formationmentioning
confidence: 99%